PECULIARITIES OF PSYCHOLOGICAL EMPOWERMENT AMONG SOCIAL WORKERS AND SOCIAL PEDAGOGUES IN THE CONTEXT OF CLIENTS’ SOCIAL INTEGRITY PROBLEMS - Kepalaitė, Albina; Vaitkeviciene, Asta; Gerulaitis, Darius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The importance of psychological empowerment with regard to employee behaviour and results of their activities was disclosed in various research. However, there is a lack of data about peculiarities of empowerment among specialists, aiming to empower subjects of their professional activities. These data would be helpful for social workers’ and social pedagogues’ work organisation, qualification, acquiring necessary skills for solving different needs of clients. Thus, the aim of this study is to disclose the peculiarities of social workers’ and social pedagogues’ psychological empowerment with regard to their clients’ social integrity problems, which they need to solve.